Robust Classification of Intramuscular EMG Signals to Aid the Diagnosis of Neuromuscular Disorders - Shobha Jose; S. Thomas George; M. S. P. Subathra; Vikram Shenoy Handiru; Poornaselvan Kittu Jeevanandam; Umberto Amato; Easter Selvan Suviseshamuthu (IEEE Open Journal of Engineering in Medicine and Biology, 2020)
Goal: This article presents the design and validation of an accurate automatic diagnostic system to classify intramuscular EMG (iEMG) signals into healthy, myopathy, or neuropathy categories to aid the diagnosis of neuromuscular diseases. Methods: First, an iEMG signal is decimated to produce a set of “disjoint” downsampled signals, which are decomposed by the lifting wavelet transform (LWT). The Higuchi's fractal dimensions (FDs) of LWT coefficients in the subbands are computed. The FDs of LWT subband coefficients are fused with one-dimensional local binary pattern derived from each downsampled signal. Next, a multilayer perceptron neural network (MLPNN) determines the class labels of downsampled signals. Finally, the sequence of class labels is fed to the Boyer-Moore majority vote (BMMV) algorithm, which assigns a class to every iEMG signal. Results: The MLPNN-BMMV classifier was experimented with 250 iEMG signals belonging to three categories. The performance of the classifier was validated in comparison with state-of-the-art approaches. The MLPNN-BMMV has resulted in impressive performance measures (%) using a 10-fold cross-validation—accuracy = $99.87± 0.25$ , sensitivity (normal) = $99.97± 0.13$ , sensitivity (myopathy) = $99.68± 0.95$ , sensitivity (neuropathy) = $99.76± 0.66$ , specificity (normal) = $99.72± 0.61$ , specificity (myopathy) = $99.98± 0.10$ , and specificity (neuropathy) = $99.96± 0.14$ —surpassing the existing approaches. Conclusions: A future research direction is to validate the classifier performance with diverse iEMG datasets, which would lead to the design of an affordable real-time expert system for neuromuscular disorder diagnosis.